Hepatitis B Virus Genotypes and Subgenotypes Circulating in Belarus - Vladimir Eremin; Fedor Karpenko; Igor Karpov; Valery Semenov; Ina Oiestad (Current Issues in Molecular Biology, 2025)
Approximately 800–900 new cases of chronic forms of hepatitis B are reported in Belarus annually. Compulsory vaccination, introduced to the country in the mid-90s, produces a certain positive effect on reducing the number of HBV cases. However, around 75,000 patients with chronic hepatitis B are estimated to live in the country at the moment. The main goal of this research was to determine the genotypes/subgenotypes of the hepatitis B virus and establish their role in maintaining the epidemic process in the country. Serological (CMIA, ELISA), molecular biological (PCR, sequencing), and bioinformatic (phylogenetic analysis) methods have been used to obtain results. As studies have shown, in 722 (81.7%) samples, genotype D has been determined; in 156 (17.7%), genotype A; in 3 (0.3%), genotype C; and only in 1 sample (0.1%), genotype B. In two cases (0.2%), a recombinant form of the hepatitis B virus has been detected. The epidemic process of hepatitis B in the country is supported mainly by the circulation of “local” variants of the virus. At the same time, there are occasional introductions of new genetic variants from outside of the country.